Sodium imbalance in pediatric intensive care practice: pathophysiology, clinical picture and treatment - Yu. V. Bykov; A. N. Obedin; A. A. Muravyeva; V. V. Fischer; E. V. Volkov; I. V. Yatsuk; O. V. Zinchenko (Вестник анестезиологии и реаниматологии)
Sodium (Na+) imbalance in the body is an urgent problem, especially in the intensive care of children. Hyponatremia (Na+ levels below 135 mmol/l) is a multifactorial condition, but the main cause of this electrolyte imbalance in children is a decrease in renal clearance in combination with high fluid intake. Hyponatremia is subdivided into three pathophysiological types: hypotonic, isotonic and hypertonic. Acute hyponatremia (< 48 hours) has the most pronounced clinical symptoms, which typically include central nervous system (CNS) dysfunction with exacerbation of hyponatremic encephalopathy and cerebral edema (CE). Severe hyponatremia in children and adolescents is treated first by infusion of a 3% solution of NaCl, with the rate and volume strictly controlled to maintain a rate of Na+ increase of no more than 12 mmol/l over a 24-hour period. Hypernatremia (Na+ levels of over 145 mmol/l) in children develops as a result of high-volume or long-term infusion of saline solutions, or as a consequence of gastroenteritis. The pathogenesis of hypernatremia involves the imbalance between consumption and excretion of fluids in the setting of reduced or absent thirst. Clinical manifestations depend on the predominant nature of the hypernatremia (hypo- or hypervolemic) and may include cerebral insufficiency (seizure syndrome, CE). Correction of hypernatremia should be performed at a rate not exceeding 0.5 mmol/l per hour or 10–12 mmol/l per day with infusion of 0.9% NaCl. Timely diagnosis and correction of hypo- and hypernatremia in pediatric intensive care practice will reduce the risk of CNS-related complications and possible death